Pertanggung Jawaban Peraturan Standar Akuntansi Keuangan Nomor 45 Terhadap Laporan Keuangan Program Kerja Badan Musyawarah Keluarga Minang Kabau Provinsi Sumatera Selatan - Rika Fitri Ramayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The situation and characteristics of the Minangkabau Family Consultative Body of the South Sumatra Province have work programs or activities. This appears related to the management of financial statements. This research in the research design used is descriptive qualitative approach. The purpose of using qualitative research methods is to disclose comparatively and in accounting for financial statements in accordance with the guideline PSAK No. 45. The results showed the weekly general cash report or transactions recorded manually in large books, and became the basis for making the budget realization report for the current year. Application of PSAK No. 45, will produce financial reports consisting of: Statements of Financial Position, Activity Reports, Cash Flow Statements and Notes to Financial Statements. The report has been presented in accordance with PSAK No. 45 of 2011. Conclusion, this standard looks more complicated but by applying this standard will produce more adequate financial statements. Keywords: PSAK Guideline Number 45, Financial Statements, Minang Kabau Family Consultative Body